Volume 4: Heat Transfer; Electric Power; Industrial and Cogeneration 1998
DOI: 10.1115/98-gt-236
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High Freestream Turbulence Levels and Length Scales on Stator Vane Heat Transfer

Abstract: Gaining a good understanding of how high freestream turbulence augments heat transfer is important for predicting thermal loadings for turbine blades and vanes. This study was aimed at documenting the surface heat transfer and the highly turbulent flowfield around a stator vane. The effects of turbulence levels between 11% and 24% were studied. At the highest turbulence level, two different Reynolds numbers (Reex = 6 × 105 and 1.2 × 106) and two different length scales were also studied. Three-component laser … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…However, as pointed out earlier, the approaching turbulence intensity and scale are much higher in this work. The low speed turbine vane turbulence data from Radomsky and Thole (1998) also demonstrated that the turbulence levels on the pressure surface were higher than those measured on the suction surface.…”
Section: Low Turbulence Heat Transfer Coefficientsmentioning
confidence: 94%
See 4 more Smart Citations
“…However, as pointed out earlier, the approaching turbulence intensity and scale are much higher in this work. The low speed turbine vane turbulence data from Radomsky and Thole (1998) also demonstrated that the turbulence levels on the pressure surface were higher than those measured on the suction surface.…”
Section: Low Turbulence Heat Transfer Coefficientsmentioning
confidence: 94%
“…The effect of freestream turbulence intensity and length scale on turbine vane heat transfer in a low speed facility was studied in detail by Radomsky and Thole (1998) …”
Section: Low Speed Turbine Vane Data -Radomsky and Thole 1998mentioning
confidence: 99%
See 3 more Smart Citations